2012
DOI: 10.1155/2012/384301
|View full text |Cite
|
Sign up to set email alerts
|

Single Agent Polysaccharopeptide Delays Metastases and Improves Survival in Naturally Occurring Hemangiosarcoma

Abstract: The 2008 World Health Organization World Cancer Report describes global cancer incidence soaring with many patients living in countries that lack resources for cancer control. Alternative treatment strategies that can reduce the global disease burden at manageable costs must be developed. Polysaccharopeptide (PSP) is the bioactive agent from the mushroom Coriolus versicolor. Studies indicate PSP has in vitro antitumor activities and inhibits the growth of induced tumors in animal models. Clear evidence of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Herbal recommendations were made to a small number of clients for a number of different conditions. A discussion of the merits of herbal supplements is outside the scope of this investigation, but there are a number of herbs and herbal formulas suggested to impart a clinical effect in veterinary species [ 47 , 48 ]. Unfortunately, herbal veterinary products have minimal regulatory oversight, as neither the Association of American Feed Control Officials (AAFCO) nor the United States Food and Drug Administration (FDA) controls these products.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal recommendations were made to a small number of clients for a number of different conditions. A discussion of the merits of herbal supplements is outside the scope of this investigation, but there are a number of herbs and herbal formulas suggested to impart a clinical effect in veterinary species [ 47 , 48 ]. Unfortunately, herbal veterinary products have minimal regulatory oversight, as neither the Association of American Feed Control Officials (AAFCO) nor the United States Food and Drug Administration (FDA) controls these products.…”
Section: Discussionmentioning
confidence: 99%
“…We also describe the pharmacology of metronomic chemotherapy in combination with a complementary/holistic approach of polysaccharopeptide (PSP) extract from the Coriolus versicolor mushroom (I'm-Yunity) and Yunnan Baiyao, two ancient Chinese medicines that have been evaluated in human cancer patients in the Chinese/Japanese medical literature. A pilot study conducted in fifteen dogs with metastatic hemangiosarcoma demonstrated encouraging results with PSP showing similar median survival times to standard doxorubicin chemotherapy (historical control data) [ 3 ]. This prompted the initiation of an ongoing pivotal clinical trial in 100 dogs with hemangiosarcoma treated with either PSP versus standard doxorubicin based chemotherapy versus the combination of chemotherapy plus PSP (personal communication with University of Pennsylvania School of Veterinary Medicine).…”
Section: Introductionmentioning
confidence: 99%
“…C. versicolor is one of the medicinal fungi commonly used in traditional Chinese medicine. Earlier studies have documented that C. versicolor PSP display diverse therapeutic activities, from inhibition of tumor cell proliferation to immunomodulation [ 7 , 27 , 28 , 29 ]. Regarding the therapeutic potential of PSP, this study modifies PSP with PEI to generate a copolymer as a gene carrier.…”
Section: Discussionmentioning
confidence: 99%